TRADE RELATIONS OF CENTRAL ASIAN KHANATES WITH NEIGHBORING STATES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article provides a scientific analysis of the history of trade relations between the Central Asian khanates and neighboring states. The role of the khanates in internal and external trade in the mid-19th century has been examined using sources and archival materials. The extent of the khanates’ large-scale external trade relations with Siberia is also highlighted.